2001
DOI: 10.1002/jemt.1154
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differences and effect of photoperiod on melatonin receptor in avian brain

Abstract: Several data suggest that melatonin may influence avian reproduction by acting at the level of the hypothalamic-hypophisial-gonadal axis, and/or on neural circuits controlling reproductive behaviours. The action of melatonin is exerted through specific receptors whose distribution and pharmacological properties have been extensively investigated. This review will focus on the distribution, sexual dimorphism, and dependence upon the photoperiod of melatonin binding sites in avian species with a special emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 101 publications
(133 reference statements)
0
15
0
Order By: Relevance
“…For example, whether melatonin receptors are co-localized within AVT-ir neurons in these brain regions is unknown. Furthermore, it is unknown whether the distribution and/or expression of melatonin receptors in green treefrogs is sexually dimorphic, as has been reported for birds (reviewed in Aste et al [2001]). While it is possible that male testosterone concentrations regulate the regional distribution of melatonin receptors, available evidence in birds and mammals suggests that melatonin receptor expression is independent of gonadal androgens [Skene et al 1993; Bentley and Ball 2000].…”
Section: Discussionmentioning
confidence: 99%
“…For example, whether melatonin receptors are co-localized within AVT-ir neurons in these brain regions is unknown. Furthermore, it is unknown whether the distribution and/or expression of melatonin receptors in green treefrogs is sexually dimorphic, as has been reported for birds (reviewed in Aste et al [2001]). While it is possible that male testosterone concentrations regulate the regional distribution of melatonin receptors, available evidence in birds and mammals suggests that melatonin receptor expression is independent of gonadal androgens [Skene et al 1993; Bentley and Ball 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on avian melatonin receptors mainly focused on the retina (Rada and Wiechmann, 2006), gonads (Aste et al, 2001) and song-control nuclei in the brain (Cassone et al, 2008;Whitfield-Rucker and Cassone, 1996) photoreception takes place in the retina only and there has been an evolutionary loss of two retinal cone classes (Barrett et al, 2003) and of certain opsins which are found in nonmammalian vertebrates including birds and fishes (Bellingham et al, 2003). These differences in circadian organisation are believed to be the consequence of a "nocturnal bottleneck" during early evolution of mammals (Foster et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings represent the first case of sexual dimorphism in IMEL binding in a mammalian brain region. The only other reported instances of sexual dimorphism in IMEL binding are in the song control system of birds and parts of the visual system and preoptic area in quail, which all displayed higher binding in males [Gahr and Kosar, 1996; Whitfield-Rucker and Cassone, 1996; Aste et al, 2001]. The reasons for these differences are unclear, but could potentially be the result of sexually dimorphic neurotransmitters, specifically GABA, which, when given at physiological doses, increases IMEL binding in several brain regions of the quail, including the preoptic area [Canonaco et al, 1994].…”
Section: Discussionmentioning
confidence: 99%